FORMULASI STRATEGI BISNIS PT. BUKIT ASAM Tbk DALAM RANGKA MENINGKATKAN PANGSA PASAR (MARKET SHARE) - Octavina, Octavina (Profit: Jurnal Adminsitrasi Bisnis, 2016)
This research is a special assessment against profit organization or state-owned PT. Bukit Asam Tbk with its main product is the product of Coal. The purpose of this paper is to determine the strengths and weaknesses (internal environment) in the PT. Bukit Asam Tbk in the midst of intense competition, to identify opportunities and threats (external environment) faced by PT. Bukit Asam Tbk amid intense competition, and analyze strategies - strategies that can be used by PT. Bukit Asam Tbk, which can effectively be used to increase sales of coal in order to increase market share amid the competition.Â Â